Perilaku Keruntuhan Balok Beton Mutu Normal Dengan Pengekangan Pada Daerah Tekan - Tahan Tahan (Media Ilmiah Teknik Sipil, 2020)
Concrete is a widely used construction material now Compared to other materials such as wood and steel. This is because the constituent material is easy to obtain, has enough strength, good durability, the making process is easy and in terms of economic price affordable. Concrete is Generally classified into two classes, namely normal quality and high quality. Both of them are now widely used in the construction activities. Normal quality concrete has a quality of 20 Mpa up to 58 MPa, while high quality concrete ranges above 58 Mpa. One of the applications in the structures is collapse behavior concrete beams on the normal quality of norm with the confinement on the pressure area. To analyze the effect of collapse behavior of normal quality concrete beams and varied Finite Element Analysis (FEA) by using ANSYS Ed. 9.0 with stirrups variation space in te respective spans (40, 80,120,150) mm and stirrup variation distance in the respective field (40,80,120,125,150,100,75.50) mm with 15/20 beam size. The steel material used has stress power of 400 each Mpa, stirrup stress 200 Mpa, normal quality stress 25 Mpa. Based on manual analysis and FEA the magnitude of ultimate capacity that occurs in the model of the beam with the dense stirrup on the stress area the ultimate moment value will rise both in the moment span area and in the field. The deformation is decreasing and the crack behavior on the pressure area can be minimized